PENGUKURAN KESEHATAN PADA KOPERASI JASA KEUANGAN SYARIAH (KJKS) BERDASARKAN PERATURAN MENTERI NEGARA KOPERASI, USAHA KECIL DAN MENENGAH RI N0.07/Per/Dep.6/IV/2016 - anwari, khairul; Ramadhani, Wahyuni (Al-Maslahah, 2018)
This research attempted to measure the financial health of Sharia Financial Services Cooperative comprehensively in accordance with the Regulation of the State Minister of Cooperatives, Small and Medium Enterprises of Indonesia. We employed Mixed Method with Convergent Model Transformation research design where the interview and financial report are predominantly data sources. The results showed that the financial performance of KJKS Kalbar Madani Year 2014-2016 are in healthy enough in the average with 77,92 score with details: (1) capital aspect fairly got score 10 with healthy category. (2) Quality side of earning asset obtained score 15,34 with less smooth category (3) Score 2,95 was given to Management aspect with good measurement. (4) Efficiency side attained score 2,5 with less good category. (5) Aspects of Liquidity acquired with illiquid category with score 2.(6) 2,25 was assessed to Independence and Growth with enough category (7) Cooperative aspect with score 5 and in useful category. (8) Aspects of Sharia Compliance year 2014-2016 earned a score of 10 with compliance category.